A de novo GRIN1 Variant Associated With Myoclonus and Developmental Delay: From Molecular Mechanism to Rescue Pharmacology - Zhang, Jin; Tang, Weiting; Bhatia, Nidhi K.; Xu, Yuchen; Paudyal, Nabina; Liu, Ding; Kim, Sukhan; Song, Rui; XiangWei, Wenshu; Shaulsky, Gil; Myers, Scott J.; Dobyns, William; et al. (Frontiers in Genetics, 2021)
N-methyl-D-aspartate receptors (NMDARs) are highly expressed in brain and play important roles in neurodevelopment and various neuropathologic conditions. Here we describe a new phenotype in an individual associated with a novel de novo deleterious variant in GRIN1 (c.1595C>A, p.Pro532His). The clinical phenotype is characterized with developmental encephalopathy, striking stimulus-sensitive myoclonus, and frontal lobe and frontal white matter hypoplasia, with no apparent seizures detected. NMDARs that contained the P532H within the glycine-binding domain of GluN1 with either the GluN2A or GluN2B subunits were evaluated for changes in their pharmacological and biophysical properties, which surprisingly revealed only modest changes in glycine potency but a significant decrease in glutamate potency, an increase in sensitivity to endogenous zinc inhibition, a decrease in response to a maximally effective concentration of agonists, a shortened synaptic-like response time course, a decreased channel open probability, and a reduced receptor cell surface expression. Molecule dynamics simulations suggested that the variant can lead to additional interactions across the dimer interface in the agonist binding domains, resulting in a more open GluN2 agonist binding domain cleft, which was also confirmed by single molecule fluorescence resonance energy transfer measurements. Based on the functional deficits identified, several positive modulators were evaluated to explore potential rescue pharmacology.